Hubungan Tingkat Pengetahuan Keluarga Dengan Upaya Pencegahan Malaria Di Unit Maranatha Desa Nolloth - Suryanti Tukiman; Yerry Soumokil; Dominggus Sahetapy (Journal of Educational Innovation and Public Health, 2024)
. Introduction: Malaria is a disease caused by parasites (protozoa) of the genus Plasmodium which are transmitted by the bite of a female Anopheles mosquito. People with malaria typically experience flu-like initial symptoms, high fever, chills, and headache. This disease can attack all age groups. Symptoms of malaria will appear after 10 days to 4 weeks in the form of fever, headache, vomiting and chills. Prevention by vector control and preventing mosquito bites to humans needs to be done to break the chain of transmission. Purpose: in this study to determine the relationship between the level of family knowledge and efforts to prevent malaria in the Maranatha Unit, Nolloth Village, East Saparua District. Method: Using a Cross Sectional design. and a total sample of 65 respondents using an instrument in the form of a questionnaire. The analysis used was the chi-squaer test. Results: there is a relationship between the level of family knowledge and efforts to prevent malaria in the Marantha Unit in Zeroth Village (p-value = 0.000). Conclusion: there is a relationship between the level of family knowledge and efforts to prevent malaria in the Marantha Unit in Zeroth Village (p-value = 0.000).